2023
DOI: 10.1101/2023.02.08.527739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ciliary ARL13B inhibits developmental kidney cystogenesis in mouse

Abstract: ARL13B is a small GTPase enriched in cilia. Deletion ofArl13bin mouse kidney results in renal cysts and an associated absence of primary cilia. Similarly, ablation of cilia leads to kidney cysts. To investigate whether ARL13B functions from within cilia to direct kidney development, we examined kidneys of mice expressing an engineered cilia-excluded ARL13B variant, ARL13BV358A. These mice retained renal cilia and developed cystic kidneys. Because ARL13B functions as a guanine nucleotide exchange factor (GEF) f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…We recently reported that Arl13b V358A/V358A mice develop kidney cysts 37 . Small cysts are visible at weaning age and become progressively larger by ~4 months of age.…”
Section: Arl13b V358a/v358a Mice Weigh Significantly More Than Contro...mentioning
confidence: 99%
“…We recently reported that Arl13b V358A/V358A mice develop kidney cysts 37 . Small cysts are visible at weaning age and become progressively larger by ~4 months of age.…”
Section: Arl13b V358a/v358a Mice Weigh Significantly More Than Contro...mentioning
confidence: 99%